Pengaruh Kinerja Keberlanjutan dan Pertumbuhan Penjualan terhadap Penghindaran Pajak pada Perusahaan Sektor Energi yang Terdaftar di BEI Periode 2021–2024 - Tria Sujarwati; Risky Budianto (AKUNTANSI 45, 2026)
This study aims to examine the effect of sustainability performance and sales growth on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This topic has become increasingly relevant in recent years due to the growing attention to corporate sustainability practices and tax transparency. Sustainability performance is measured using Environmental, Social, and Governance (ESG) scores. Sales growth is measured based on the increase in sales from year to year, while tax avoidance is proxied by the Cash Effective Tax Rate (CETR). This research employs a quantitative approach, with the sample determined using a purposive sampling method. Based on the established criteria, a total of 52 energy sector companies were selected as the research sample. The data were analyzed using multiple linear regression with the assistance of IBM SPSS 26. The results indicate that sustainability performance has no significant effect on tax avoidance. Similarly, sales growth does not have a significant effect on tax avoidance.